Intuitionistic fuzzy multi-objective linear programming problem with various membership functions - Singh, Sujeet Kumar; Yadav, Shiv Prasad (Annals of operations research, 2018)
This study addresses intuitionistic fuzzy multi-objective linear programming problems using triangular intuitionistic fuzzy numbers with mixed constraints. We convert the problem into single objective fuzzy programming problem. Then using different types of membership functions (linear and nonlinear), we transform the problem into crisp linear/non-linear programming problem, which is solved by suitable crisp programming approaches. The methodology is demonstrated with the help of a numerical example and the usefulness of various membership functions is discussed.